2013
DOI: 10.1038/srep02875
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs conferring resistance to downy mildew in legacy cultivars of lettuce

Abstract: Many cultivars of lettuce (Lactuca sativa L.), the most popular leafy vegetable, are susceptible to downy mildew disease caused by Bremia lactucae. Cultivars Iceberg and Grand Rapids that were released in the 18th and 19th centuries, respectively, have high levels of quantitative resistance to downy mildew. We developed a population of recombinant inbred lines (RILs) originating from a cross between these two legacy cultivars, constructed a linkage map, and identified two QTLs for resistance on linkage groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Some lettuce cultivars such as Iceberg and Grand Rapids exhibit resistance at the adult plant stage in the field that cannot be attributed to Dm genes (Milbrath 1923;Verhoeff 1960;Crute and Norwood 1981). This quantitative resistance phenotype (Norwood and Crute 1985;Grube and Ochoa 2005) has so far been shown to be inherited polygenically (Simko et al 2013); transgressive segregation resulting in elevated resistance has been observed in progeny from cvs. Grand Rapids 9 Iceberg (Grube and Ochoa 2005;Simko et al 2013).…”
Section: Genetics Of Resistance and Nomenclature Of Resistance Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lettuce cultivars such as Iceberg and Grand Rapids exhibit resistance at the adult plant stage in the field that cannot be attributed to Dm genes (Milbrath 1923;Verhoeff 1960;Crute and Norwood 1981). This quantitative resistance phenotype (Norwood and Crute 1985;Grube and Ochoa 2005) has so far been shown to be inherited polygenically (Simko et al 2013); transgressive segregation resulting in elevated resistance has been observed in progeny from cvs. Grand Rapids 9 Iceberg (Grube and Ochoa 2005;Simko et al 2013).…”
Section: Genetics Of Resistance and Nomenclature Of Resistance Genesmentioning
confidence: 99%
“…This quantitative resistance phenotype (Norwood and Crute 1985;Grube and Ochoa 2005) has so far been shown to be inherited polygenically (Simko et al 2013); transgressive segregation resulting in elevated resistance has been observed in progeny from cvs. Grand Rapids 9 Iceberg (Grube and Ochoa 2005;Simko et al 2013). Some cultivars such as Green towers and Cobham Green have no known Dm genes and are used as susceptible lines to grow B. lactucae isolates; however, the European isolate Serr84/99 is avirulent on Cobham Green and there is some evidence suggesting polygenic resistance in this cultivar (Maisonneuve 2011b).…”
Section: Genetics Of Resistance and Nomenclature Of Resistance Genesmentioning
confidence: 99%
“…Lettuce is a diploid, self-pollination species with 2n = 2x = 18 chromosomes. Based on plant morphology, lettuce can be classified into four types including iceberg lettuce, romaine lettuce, butterhead lettuce and non-heading leaf-type lettuces (Simko et al, 2013). Unlike most other flowering plants, transition from vegetative to reproductive phase in lettuce is induced by high temperatures, and followed by rapid stem elongation (bolting) and flowering (Fukuda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In each experiment, seeds were planted in two or three complete blocks to produce approximately 30 plants of each RIL and parent per plot. Disease assessment was done by scoring disease severity on a scale ranging from 0 (no disease) to 5 (severe disease) for each plot (Simko et al, 2013). Disease assessments were performed at market maturity.…”
Section: Methodsmentioning
confidence: 99%